Cigarette Smoking and Risk of Different Pathologic Types of Stroke: A Systematic Review and Dose-Response Meta-Analysis - Luo, Jianyu; Tang, Xiaorong; Li, Fan; Wen, Hao; Wang, Lin; Ge, Shuqi; Tang, Chunzhi; Xu, Nenggui; Lu, Liming (Frontiers in Neurology, 2022)
Objectives To quantify the association of cigarette smoking, including cigarettes per day and quitting duration, with the risk of different types of stroke morbidity and mortality in the general population, and to clarify the shape of the dose-response relations. Study Selection Prospective cohort studies and reported on the association between smoking, quitting and the incidence or mortality of stroke were included. Data Extraction and Synthesis All available data were converted uniformly to odds ratios (ORs) and were pooled using random-effects meta-analysis with inverse variance weighting. A dose-response meta-analysis was performed to explore the quantitative relationship between different smoking characteristics and the risk of different pathologic types of stroke incidence. Results Twenty-five studies with 3734216 individuals were included. Compared to never smokers, the pooled ORs of stroke morbidity and mortality were 1.45 (1.24 to 1.70) and 1.44 (1.23 to 1.67) among ever smokers and 1.90 (1.55 to 2.34) and 1.70 (1.45 to 1.98) among current smokers. The risk of different pathologic types of stroke was also increased among ever and current smokers. There was a significant nonlinear dose-response association between the number of cigarette smoking and the risk of stroke incidence. Comparing no smoking, the ORs for smoking five and 35 cigarettes per day were 1.44 (1.35 to 1.53) and 1.86 (1.71 to 2.02). Other pathologic types of stroke have a similar dose-response relationship. There was also nonlinear dose-response association between the length of time since quitting and risk of stroke. The risk of stroke decreased significantly after quitting for three years (OR = 0.56 (0.42 to 0.74)). Conclusion The risk of different types of stroke among smokers is remarkably high. Our findings revealed a more detailed dose-response relationship and have important implications for developing smoking control strategies for stroke prevention.